Effect of Roasting on Functional Properties, Phytochemical Composition and Antioxidant Activity of Watermelon Seed Flour - Imran, Ifa; Joseph, Namitha Prastheena (Asian Journal of Biological and Life Sciences)
Background: Watermelon seeds are byproducts of watermelon with significant nutritional, therapeutic and functional potentials but they are often discarded as waste. The present study analyzed the effect of roasting on the functional properties, phytochemical contents and antioxidant activity of watermelon seed flour. Materials and Methods: Flour made from both dried, deshelled, roasted and unroasted watermelon seeds were analyzed for functional properties, phytochemical contents and antioxidant activity respectively. Results: The results revealed that roasting brought about a reduction in antioxidant activity as well as phytochemical contents such as alkaloid, saponin and flavonoid. However, the roasted watermelon seed flour exhibited a significant increase in the functional properties such as water absorption capacity and oil absorption capacity compared to the unroasted watermelon seed flour. Conclusion: Thus, these findings indicate that roasting reduces some health-promoting compounds but at the same time improves the flour’s functional properties, thereby making it more suitable for food formulations that require better binding, moisture retention, and oil absorption.
Keywords: Antioxidant activity; Functional properties; Phytochemical composition; Watermelon seed flour.